2014
DOI: 10.1163/15685381-00002949
|View full text |Cite
|
Sign up to set email alerts
|

Individual variation in the advertisement calls of a Neotropical treefrog (Scinax constrictus)

Abstract: A bstract. Studies of the variability of signals at different levels are important to resolve issues related to the evolution of a species' recognition system. We analysed the variation within males, among individuals, and among three breeding seasons in the advertisement calls of Scinax constrictus, a Neotropical hylid frog endemic to the Cerrado of Brazil. We assessed the influence of different temperature ranges and different body condition ranges over a three-year period of breeding season on the acoustica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 55 publications
2
26
0
Order By: Relevance
“…Similar results could be found elsewhere [2,5,8,19,20]. In M. achatina, properties that contribute most to individual discrimination are pulse duration, dominant frequency and call duration.…”
Section: Individual Distinctivenesssupporting
confidence: 89%
See 1 more Smart Citation
“…Similar results could be found elsewhere [2,5,8,19,20]. In M. achatina, properties that contribute most to individual discrimination are pulse duration, dominant frequency and call duration.…”
Section: Individual Distinctivenesssupporting
confidence: 89%
“…Previous studies of frogs' call have shown that some acoustic properties demonstrate a high level among-individual variation and these properties could potentially be used as individual identity [2,5,8]. Among all of the properties, temporal properties are components that contribute mostly to individual distinctiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Full-size  DOI: 10.7717/peerj.8708/ fig-1 was higher than CV W (Morais et al, 2012;Gambale, Signorelli & Bastos, 2014;Turin, Nali & Prado, 2018). Calls were pooled by individual specimens.…”
Section: Data Analysesmentioning
confidence: 99%
“…Advertisement calls are a form of male anuran vocalization that is most commonly heard and of the highest value in taxonomy and they play a crucial role in attracting potential mates and conveying territorial information to conspecifics. Several researchers have focused on advertisement calls of anurans (Wells, 2007;Gambale, Signorelli & Bastos, 2014;Köhler et al, 2017;Poyarkov et al, 2019;Wei et al, 2019). The variation in advertisement calls in anurans is generally studied at the intraspecific and interspecific levels (Köhler et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation